PERLINDUNGAN HAK PATEN ATAS JAMU KAITANNYA DENGAN PENGETAHUAN TRADISIONAL DI INDONESIA - MIEKE IRENE HUTABARAT (PREMISE LAW JURNAL, 2017)
In its development, Indonesia as a developing country has abundance of traditional knowledge and geographical indication although it does not maximally realize its potential because of weakness in knowledge, skill, professionalism in human resources and funds. This condition is used by developed countries that are more advanced in technology, financial and technical skill, and the operation of various multinational companies. Since it has the variety of traditional knowledge and great culture, Indonesia today becomes of hijacking from foreign countries. Foreigners learn, search for, patent and sell traditional medical science and indigenous medical plants with high price to the third world. The research used judicial normative method by analyzing legal provisions in patent rights under Law No. 13 of 2016 on Patents and some other literatures related to Paten Rights on Traditional Jamu in Indonesia. Keywords : Patent, Traditional herbal medicine, Judicial review.